2023
DOI: 10.3390/nu15040863
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation to Improve Sarcopenia in Chronic Liver Disease: Facts and Perspectives

Abstract: Creatine supplementation has been one of the most studied and useful ergogenic nutritional support for athletes to improve performance, strength, and muscular mass. Over time creatine has shown beneficial effects in several human disease conditions. This review aims to summarise the current evidence for creatine supplementation in advanced chronic liver disease and its complications, primarily in sarcopenic cirrhotic patients, because this condition is known to be associated with poor prognosis and outcomes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…[45] Furthermore, creatine supplementation has proven effective for managing sarcopenia among older adults and may hold promise for ameliorating muscle wasting associated with chronic liver disease and cancer. [48][49][50] To concluded, amino acids and their associated substances can help to combat muscle atrophy by regulating energy metabolism and maintaining protein homeostasis. Additionally, leucine and HMB are often used alongside other nutrients, such as vitamins, for better outcomes.…”
Section: Mechanism Of Action Preclinical Evidence Clinical Evidencementioning
confidence: 99%
“…[45] Furthermore, creatine supplementation has proven effective for managing sarcopenia among older adults and may hold promise for ameliorating muscle wasting associated with chronic liver disease and cancer. [48][49][50] To concluded, amino acids and their associated substances can help to combat muscle atrophy by regulating energy metabolism and maintaining protein homeostasis. Additionally, leucine and HMB are often used alongside other nutrients, such as vitamins, for better outcomes.…”
Section: Mechanism Of Action Preclinical Evidence Clinical Evidencementioning
confidence: 99%
“…At least 60% of cirrhotic patients awaiting LT are malnourished, mainly because of insufficient food intake [ 127 , 128 ]. Indeed, Ferreira et al demonstrated that a negative energy balance (obtained by subtracting total caloric intake from total energy expenditure), mostly due to inadequate food intake, was present in 78.1% of cirrhotic patients awaiting LT [ 129 ].…”
Section: Nutritional Management Strategies Before Lt Patientsmentioning
confidence: 99%
“…However, studies found high heterogeneity in BCAA dosage (6 to 110 g/day) and supplementation duration (3 to 12 months). Therefore, more research is needed to define the BCAA dosage and timing to prevent/treat sarcopenia in CLD patients, including the optimal combination of BCAA and resistance training to maximise the effect on muscle mass and function [ 237 ].…”
Section: Sarcopeniamentioning
confidence: 99%